2018
DOI: 10.1128/mcb.00041-18
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1α and Cofilin Regulate Nuclear Translocation of NF-κB and Promote Expression of the Anti-Inflammatory Cytokine Interleukin-10 by T Cells

Abstract: While several protein serine/threonine kinases control cytokine production by T cells, the roles of serine/threonine phosphatases are largely unexplored. Here, we analyzed the involvement of protein phosphatase 1α (PP1α) in cytokine synthesis following costimulation of primary human T cells. Small interfering RNA (siRNA)-mediated knockdown of PP1α (PP1) or expression of a dominant negative PP1α (D95N-PP1) drastically diminished interleukin-10 (IL-10) production. Focusing on a key transcriptional activator of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…We also measured an increase in PKCζ/λ (T410/T4033) and cofilin (S3) phosphorylation at the 2-day time point with both single and combined kinase inhibition ( Figure S5). Cofilin is an actin depolymerizing factor known to regulate actin dynamics and cell invasion; however, recent studies have established the role of cofilin in NFκB nuclear translocation [31,32]. The atypical protein kinase C member PKCζ is involved in several survival pathways that are deregulated in cancer and is also involved in the activation of NFκB [33,34].…”
Section: Kinome Response To Combined Met and Mek Inhibition In Nf1-rementioning
confidence: 99%
“…We also measured an increase in PKCζ/λ (T410/T4033) and cofilin (S3) phosphorylation at the 2-day time point with both single and combined kinase inhibition ( Figure S5). Cofilin is an actin depolymerizing factor known to regulate actin dynamics and cell invasion; however, recent studies have established the role of cofilin in NFκB nuclear translocation [31,32]. The atypical protein kinase C member PKCζ is involved in several survival pathways that are deregulated in cancer and is also involved in the activation of NFκB [33,34].…”
Section: Kinome Response To Combined Met and Mek Inhibition In Nf1-rementioning
confidence: 99%
“…This is in agreement with our findings that PPP1R11 did not alter the NF‐κB signaling molecules studied despite affecting NF‐κB target genes. Another very recently published study confirmed that PP1A affected NF‐κB signaling in T cells and consequently cytokine expression including IL‐2, IL‐10, and to a lesser extent IFN‐γ. However, it needs to be noted that the authors used PHA‐stimulated T cell blasts that were expanded in IL‐2‐containing medium before use for functional studies and costimulation, and hence the comparability to our study may be limited, while Mock et al .…”
Section: Discussionmentioning
confidence: 76%
“…Hence, therapeutic targeting of these noncatalytic subunits may offer a unique opportunity for context‐specific modulation of PP1. Importantly, PP1A has been recently shown to be involved in T cell activation and cytokine expression via augmenting TCR‐induced NF‐κB activation without affecting classical upstream NF‐κB signaling molecules . PPP1R11 itself has been shown to be involved in apoptosis and cell cycle regulation chiefly by regulating the conformation of PP1 and affecting its interaction with PIPs rather than regulating gene expression of PP1 …”
Section: Introductionmentioning
confidence: 99%
“…Upon cell activation, I κ B is phosphorylated and degraded, and the NLS is unmasked, leading to the nuclear transport of NF- κ B. The translocation in the nucleus is thought to contribute to the inflammatory gene expressions [ 47 , 48 ]. The levels of inflammatory factors such as IL2, IL6, TNF α , IFN γ , MCP-1, ICAM-1, vascular adhesion molecule 1 (VCAM-1), and toll-like receptor 4 (TLR-4) are reported to be downregulated by the inhibition of NF- κ B p65 nuclear translocation [ 23 , 49 ].…”
Section: Discussionmentioning
confidence: 99%